Search for simultaneous and parallel cosmic gamma rays in the balloon-borne emulsion telescope experiments (GRAINE2015). (February 2019) - Yamamoto, Saya; Iyono, Atsushi; Aoki, Shigeki; Takahashi, Satoru; Rokujo, Hiroki; Mizutani, Fukashi; Hamada, Kaname; Hara, Toshio; Inoue, Tatsuki; Ishiguro, Katsumi; Kawahara, Hiroaki; Kodama, Koichi; et al.
Abstract: The emulsion chamber telescopes for observing 10 MeV - 100 GeV gamma rays have been developed by GRAINE (Gamma Ray Astro-Imager with Nuclear Emulsion) projects. We have performed the balloon filight in May, 2015 at Alice Springs, Australia, with 14.4 hours duration (including 11.5 hours of level flight) and 0.378 square meter aperture (GRAINE2015). GRAINE experiments utilized the multiple stage systems of emulsion films for timestamper of registered tracks. In this paper, we report the potential of GRAINE2015 experiments to detect the parallel and simultaneous cosmic gamma rays such as charged particles due to hadronic interactions, EAS (Extensive Air Shower) and GRBs (Gamma Ray Bursts).